The content of riboflavin and its coenzymes forms in the brain of rats of different ages - N. L. Fedorko; S. S. Petrov; K. V. Nikolaienko (Journal of Education, Health and Sport, 2017)
The content of total riboflavin and its coenzymes (FAD and FMN) in the brain homogenates of rats of different ages by means of fluorimetric ion exchange chromatography was determined. The experiment included 3 age groups of rats: 3 months, 10-12 months, and the old 22-24 months.